Women in German literature - Dhahir, Thamer Abdulkareem (International Journal of Psychosocial Rehabilitation, 2026)
Woman … proverb says that she is the half of society mother, sister, daughter and wife. But alas for a long time through all ages of the huge history of the human life this half had exposed to role ignorance and most of cultures put her under depression. So it was a normal result for that kind of female treatment to be even ignored in the intellectual lighted side which is the literature... In this research we just give a simple glimpse about the position of the German women during some periods of time and specially her existing character and role in the German literature. And may be the reader gets surprised when he knows that it was not permissible for a woman in an era in Germany to have a single book or to get educated because young wives of workers were taught that their home is the holy land and were told that their kids and husbands are the masters of that land the only job is the responsibility for making happiness at home and she has to live according to the economic circumstances of the family and strict power of her father till she gets married and came under control of the husband through the different social classes and Sometimes When women got chance for participating in writing they have to raise the standard of life and profit only not for creativity because of marital abandonment, widowhood or kids auspices. Also it is important to mention women’s right movements during at least two generations to start new liberal agreement of gender And the stages of forming women’s political parties to demand the active participation of her role. A simple glimpse about the usage of woman’s roles in the Nazi time with the guidance Adolf Hitler presenting the political agenda of Berlin policy as pilots. In This research you will find some famous female German names that affected in the history of the Frankish woman such as Elisabeth Selbert and her role in women’s rights movements… Briefly The German woman lived, the struggle between the overwhelming general presence of female idealism and the paradigm cited by women’s difficulties and left for the history an indelible mark on the stories and articles she produced.